Analysis of Micro-Level Social Determinants on The Incidence of Stunting in Kediri City: A Qualitative Study - Winarti, Eko; Susmiati, Susmiati; Alimansur, Moh; Jayani, Indah; Susilowati, Erna (Media Publikasi Cendekia Indonesia, 2025)
Stunting is a serious health problem that has long-term impacts on children's physical and cognitive growth and national progress. This study aims to explore micro-level social determinants, such as maternal knowledge, caregiving practices, household food access, and health service utilization, that influence stunting in Kediri City, and to formulate context-based strategies to address these issues. The design of this study uses a qualitative approach with a case study method; Data were collected through in-depth interviews and participatory observations of mothers who have toddlers or school-age children. Based on research, the incidence of stunting in Kediri City is influenced by various factors, including: lack of understanding of balanced nutrition, inadequate nutritional intake, malnutrition from an early age, lack of monitoring during pregnancy, Low Birth Weight (LBW), unhealthy eating habits, to recurring child health problems, lack of food variety and limited time and knowledge of mothers also exacerbate the situation. These findings emphasize the importance of nutrition education from pregnancy, improving primary health services such as routine visits to health centers, and continuous monitoring of child growth and development. This study recommends a multisectoral and participatory approach to accelerate the reduction of stunting at the community level.